Expert systems and knowledge management for failure prediction to onshore pipelines: Issue to industry 4.0 implementation - Buccieri, Gilberto Pachoal [UNESP]; Muniz, Jorge [UNESP]; Balestieri, José Antonio Perrella [UNESP]; Matelli, José Alexandre [UNESP] (FapUNIFESP (SciELO), 2020)
The paper aims to propose an Expert System to predict the failure of onshore pipelines. Knowledge Management supports expertise sharing throughout the organization. The Expert System Prototype Model proposed is classified as Empirical Descriptive Research, and may support maintenance management. The findings evidence that Expert System proposed grounded in employee knowledge may be considered a promising solution to support Industry 4.0 implementation. The Expert System facilitates the decision-making of the experts so that the employees' expertise can be better used in the implementation of Industry 4.0 and to face the new challenges related to the daily work in the organization. In this context, the Expert System can be considered as an innovative approach to manage maintenance processes and supporting reliable, consistent decisions during I.4 implementation.
Sistemas especialistas e gestão do conhecimento para previsão de falhas em dutos terrestres: Uma questão para a implementação da indústria 4.0
Keywords: Expert system; Industry 4.0; Knowledge management; Maintenance